EXCHANGE NAILING FOR NON-UNION OF FEMORAL SHAFT FRACTURES - Razaq, Mohammad Naeem-ur-; Qasim, Muhammad; Sultan, Shahid (Journal of Ayub Medical College Abbottabad, 2010)
Background: There are many ways to treat aseptic non-union of femoral shaft fractures with reported varied success rate. Amongst all these, Exchange nailing is the simplest and most successful technique for treating aseptic non union of femoral shaft fractures. We have carried out a prospective study in the Department of Trauma & Orthopaedics, Ayub Medical College Abbottabad to analyse the role of exchange nailing for aseptic non union of femoral shaft fractures. Methods: Forty-three femoral shaft aseptic non-unions in 41 consecutive patients were treated using exchange IM nailing, from January 2006 to December 2007. The inclusion criteria for patients in the study was a femoral shaft fractures' aseptic non-union, has less than 1 Cm shortening with no segmental bone defect, and a radiolucent line of the non-union, and which had previously been treated by intra-medullary nail. The surgical technique included removal of previously inserted intra-medullary nail, reaming of medullary cavity up to 2 mm above the previous size, and re-insertion of statically locked exchange intra-medullary nail. Results: Forty-three femoral shaft aseptic non-union in 41 patients were treated; the mean age of the patients was 38.81±13.75 years. Thirty-nine non-union out of total 43 cases (39/43) had healed giving a union rate of 90%. Non-union persisted in the remaining four cases (4/43) in-spite of extended post operative follow up of these patients for 18 months. Mean union was 4.97±1.53 months. No major surgical complications were noted. Conclusion: Exchange nailing is a simple technique for treating aseptic non union of femoral shaft fractures. Based on the results of our study, we recommend it as the procedure of choice for non comminuted, aseptic non union of femoral shaft fracture. Keywords: Aseptic non-union, femoral non-union, exchange interlocking intra-medullary nailing